A little princess - Burnett, Frances Hodgson, 1849-1924. (London : Wodsworth, 1994)
Sara Crewe, a pupil at Miss Minchin's London school, is left in poverty when her father dies but is later rescued by a mysterious benefactor.
6.0
3-6
Keywords: Orphans -- Juvenile fiction; Schools -- Juvenile fiction; Orphans -- Fiction; Schools -- Fiction; Orphans -- Fiction; School stories; London (England) -- Juvenile fiction; London (England) -- Fiction; London (England) -- Fiction